Reporting Research : A Biologist's Guide to Articles, Talks, and Posters - Clymo, R. S. (Cambridge : Cambridge University Press, 2014)
Want to learn how to present your research successfully? This practical guide for students and postdoctoral scholars offers a unique step-by-step approach to help you avoid the worst, yet most common, mistakes in biology communication. Covering irritants such as sins of ambiguity, circumlocution, inconsistency, vagueness and verbosity, misuse of words and quantitative matters, it also provides guidance to design your next piece of work effectively. Learn how to write scientific articles and get them published, prepare posters and talks that will capture your audience and develop a critical attitude towards your own work as well as that of your colleagues. With numerous practical examples, comparisons among disciplines, valuable tips and real-life anecdotes, this must-read guide will be a valuable resource to both new graduate students and their supervisors.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).